TransOral Endoscopic Thyroidectomy via Submental and Vestibular Approach: A Preliminary Report - Fu, Yilong; Wu, Mengwei; Fu, Jinbo; Lin, Suqiong; Song, Zhengfu; Chen, Jiyu; Yan, Wei; Kuang, Penghao; Lin, Fusheng; Luo, Yezhe; Lin, Ende; Hong, Xiaoquan; et al. (Frontiers in Surgery, 2020)
Purpose: Transoral endoscopic thyroidectomy via vestibular approach (TOETVA), with its excellent cosmetic effect, has become increasingly popular worldwide. Nonetheless, anatomic obstacles have limited its development to a certain extent. Here, we present our preliminary outcomes of transoral endoscopic thyroidectomy via submental and vestibular approach (TOETSMVA), which can overcome those limitations. Methods: From November 2019 to March 2020, we performed TOETSMVA in 21 consecutive patients with thyroid carcinoma at Zhongshan Hospital, Xiamen University. A 1.5-cm lateral incision was made at two fingers below the mandible; two 5-mm incisions were made in the vestibule near the first molars; TOETSMVA was completed through these incisions. The demographic data and surgical outcomes of the patients were retrospectively reviewed. Results: Twenty-one patients with a mean age of 37.5±10.4 years were incorporated into this study. Fourteen patients had papillary thyroid micro-carcinomas, two had papillary thyroid carcinomas, and five had benign nodules. Eight patients had lymph node metastases. All surgeries were performed successfully without conversion to open thyroidectomy. The mean operation time was 138.8±33.2 min; the average hospital stay was 3.3±0.8 days. No patients developed cutaneous paralysis in the midline chin region. Transient recurrent laryngeal nerve paralysis was observed in one patient. There was no evidence of postoperative bleeding, infection, tetany, or other complications. Conclusion: TOETSMVA was shown to be a safe and advisable alternative for selected patients. This approach can overcome the limitations of TOETVA without sacrificing cosmetic results.